Survei Motivasi Masyarakat dalam Mengikuti Komunitas Olahraga di Komplek GOR Tri Lomba Juang Semarang - Ahmad Toyib; Tommy Soenyoto (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine and analyze the level of community motivation in participating in the sports community in the GOR Tri Lomba Juang Semarang Complex. This type of research is descriptive quantitative with the population of this study are members of the sports community in the complex of GOR Tri Lomba Juang Semarang. The number of samples used was 30 respondents with data collection techniques randomly sampling technique. Data collection techniques using a questionnaire. The data analysis method used is descriptive percentages. The results showed that the motivation of the community in participating in the sports community, especially members of the sports community, was classified as very high with an overall percentage score of 87,3%. While the remaining 12,7% of respondents have moderate motivation and 0% low motivation in sports activities that are recreational in nature, especially the sports community in the GOR Tri Lomba Juang Semarang complex. The conclusion from the research results is that in general, people have high motivation in participating in the sports community in the GOR Tri Lomba Juang Semarang complex to maintain health